Development of Test Instruments Based on Revision of Bloom's Taxonomy to Measure the Students' Higher Order Thinking Skills - Oktaviana, Dwi; Susiaty, Utin Desy (Universitas PGRI Madiun, 2020)
The objectives of this study were to determine: (1) the appropriateness of the comparative material test instrument based on the Revised Bloom Taxonomy to measure HOTS student; (2) the quality of the comparative material test instrument based on the Revised Bloom Taxonomy to measure HOTS student; and (3) analysis of potential effects on the use of test instruments for comparison material based on Revised Bloom's Taxonomy to measure HOTS students'developed. This research is development research with the Tessmer model development design. The subjects of this research were all students of class VIII SMP Koperasi Pontianak. The research data was obtained based on the expert's / expert's assessment of the test instrument, the results of the test small group which will be analyzed in terms of validity, difficulty index, distinguishing power, and item reliability, as well as the results of the tests field test which will be analyzed related to potential effects. The results showed that: (1) the feasibility of the comparative material test instrument based on the Revised Bloom Taxonomy to measure HOTS students'reached the valid criteria level; (2) the quality of the comparative material test instrument based on the Revised Bloom Taxonomy to measure the HOTS of students reaching the criteria level is valid, difficult, has poor distinguishing power, and is declared to have low feasibility as a research instrument; (3) analysis of potential effects on the use of test instruments for comparison material based on Revised Bloom's Taxonomy to measure HOTS to student achieve an effectiveness level of 68.96% with the criteria for positive potential effects.